2021
DOI: 10.1002/cam4.4136
|View full text |Cite
|
Sign up to set email alerts
|

Predictive role of diffusion‐weighted whole‐body MRI (DW‐MRI) imaging response according to MY‐RADS criteria after autologous stem cell transplantation in patients with multiple myeloma and combined evaluation with MRD assessment by flow cytometry

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…WB-MRI is currently used to detect focal lesions and determine the indication of treatment according to the IMWG criteria 12 . Moreover, recent studies demonstrated the efficacy of repetitive WB-MRI for treatment response and prognostic impact 7 9 . LSV, which could be additionally evaluated in the WB-DWI of diagnostic process, could become an additional and simplified prognostic indicator in patients with NDMM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…WB-MRI is currently used to detect focal lesions and determine the indication of treatment according to the IMWG criteria 12 . Moreover, recent studies demonstrated the efficacy of repetitive WB-MRI for treatment response and prognostic impact 7 9 . LSV, which could be additionally evaluated in the WB-DWI of diagnostic process, could become an additional and simplified prognostic indicator in patients with NDMM.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with MM, the use of WB-DWI in diagnosis is superior to whole-body radiographs 4 and is equal to or more sensitive than PET/CT for the detection of focal lesions 1 , 5 , 6 . Although WB-DWI is mainly used in diagnostic process, there are several reports regarding the use of WB-DWI to monitor the patient’s response to treatment 7 9 . Myeloma Response Assessment and Diagnosis System (MY-RADS) recommendation was designed to report WB-MRI and assess treatment response 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DW-MRI has been applied to MM because of its relatively excellent sensitivity compared with FDG PET/CT and whole-body low-dose CT (9). DW-MRI has been proven to be an effective tool not only for MM diagnosis but also for outcome prediction after chemotherapy, exerting an increasing influence on the treatment management of MM (10). Even though DW-MRI is now gradually replacing traditional imaging methods of MM diagnosis (11), its implementation is not complete in predicting survival due to lack of relevant studies.…”
Section: Introductionmentioning
confidence: 99%
“…Whole-body diffusion-weighted MRI (WB-DWI) maintains the advantages of MRI to identify small lesions in bone marrow at diagnosis, but it also allows the quantification of residual disease through the apparent diffusion coefficient without the need for intravenous contrast and shows a good correlation with bone marrow infiltration, thus being superior to conventional MRI (91,92). Some preliminary studies have confirmed a benefit in PFS linked to the achievement of WB-DWI negativity after ASCT (93,94), additionally being a technique without ionizing radiation, which may overcome some of the limitations of PET-CT (95).…”
Section: Towards a Comprehensive Evaluation Of Tumor Burden: The Futurementioning
confidence: 99%